Scenario modeling of the stability of the russian budget system against external economic shocks in 2013–2015 - Frolov, I. E.; Makedonskii, S. N.; Shirov, A. A. (Studies on Russian economic development, 2013)
The results of forecast modeling of the Russian budget system’s stability against external economic shocks are presented in the paper. Two scenarios are considered: Scenario 1 or “short-term crisis” with its acute phase lasting about three quarters (similarly to the crisis of 2008–2009) and Scenario 2 or “protracted crisis,” which implies a duration of crisis phenomena of about a year and a half (to put it hypothetically, in 2013–2014). On the basis of the scenario forecast modeling results, the conclusion is drawn that regional budgets are the weakest link of the Russian budget system. The crisis period is characterized by an urgent necessity of handing over a part of tax revenues received by the federal budget to the regional level and increasing money transfers to the budgets of federal subjects.